2018
DOI: 10.2319/092917-659.1
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone receptor gene is related to root length and tooth length in human teeth

Abstract: The results indicate that the GHR rs6184 variant is associated with tooth length and ratio dimensions in a Japanese cohort. Further studies utilizing a larger sample size are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Some studies have reported that the length from the root to the top of the crown was about 20.7 mm and 21.1 mm in the maxillary and mandibular first molars respectively (Verhoeven et al 1979;Viecilli et al 2013;Hikita et al 2018). In our study, the maximum lengths were 20.6 mm and 21.4 mm in the maxillary and mandibular first molars respectively (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Some studies have reported that the length from the root to the top of the crown was about 20.7 mm and 21.1 mm in the maxillary and mandibular first molars respectively (Verhoeven et al 1979;Viecilli et al 2013;Hikita et al 2018). In our study, the maximum lengths were 20.6 mm and 21.4 mm in the maxillary and mandibular first molars respectively (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…In this context, the association between variants of the GHR coding gene and craniofacial tissue phenotypes has been exhaustively addressed [ 4 ]. However, since 2013, new GHR variants, such as P561T, rs6184 SNP and rs6180, have been identified as associated, in one hand, with the face mandibular morphology and tooth dimensions [ 2 , 9 , 86 ] and, in the other hand, with developmental defects of enamel [ 12 ]. Recently Marañón-Vásquez et al showed that genetic polymorphisms in GHR (rs2973015) and IGF2R (rs2277071) have been associated with variations in craniofacial dimensions [ 87 ].…”
Section: Gh/igf Axis Modulates the Morphology Of The Dento-alveolar Complex And Cranio-facial Bonesmentioning
confidence: 99%
“…Among the various hormones and growth factors investigated, GH appears to be one of the most closely associated with dental maturity [ 8 ]. Recent studies have shown that GHR variants (rs6184 and rs6180) are associated with specific tooth and root dimensions [ 9 , 10 ], as well as with mandibular morphology [ 11 ]. Genetic polymorphisms in GHR (rs1509460) are also associated with developmental defects of enamel arguing for the GHR contribution to dental enamel synthesis and structure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the results of the study by Hikita et al . [15] The authors found relationship of GHR variant rs6184 with RLs and tooth length for the upper and lower lateral incisors and upper canines.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hikita et al . [15] found 46.6% and 8.1% allele frequencies of GHR variants for rs6180 and rs6184.…”
Section: Discussionmentioning
confidence: 99%